(untitled) (Research, Society and Development, 2021)
The concern with the animal’s welfare has become increasingly frequent and the use of cattle in sporting events has aroused discussions about the preservation and integrity of these animals. The objective of this work was to evaluate whether the cattle participating in the team roping modality receive all support regarding the animal welfare criteria. During the 41st National Championship of the Quarter Horse Breed of Work and Conformation, aspects of animal welfare of 410 cattle that participated in the team roping were evaluated. Behavioral aspects were observed before, during and after the end of the competition, in addition to quantifying the number of runs per animal, the presence of ectoparasites, thermal comfort, food and hydration. It was possible to conclude that the environment in which the tests were carried out, the feeding conditions, the space and the thermal comfort meet the criteria of animal welfare.